2014
DOI: 10.1039/c4ob00852a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3,3-disubstituted-2,3-dihydroazanaphthoquinones via simultaneous alkyne oxidation and nitrile hydration of ortho-alkynylarenenitriles

Abstract: o-Alkynylarenenitriles when heated with Pd(OAc)2/H2O/(±)-CSA in DMSO undergo simultaneous alkyne oxidation and nitrile hydration to give 3-aryl-3-hydroxy-2,3-dihydroazanaphthoquinones. Upon treatment with (±)-CSA, these compounds form 3-arylazanaphthoquinones in situ, which add to electron-rich aromatics and terminal alkene/alkyne to afford 3,3-disubstituted-2,3-dihydroazanaphthoquinones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…100 Related examples where DMSO has been used as an additive in palladium catalysed reactions have appeared and while we do not intend to cover these cases due to the unclear role DMSO is playing in these reactions, selected examples can be found in the reference section. 103,104 Palladium bissulfoxide systems in catalysis 45 In initial work, White and co-workers showed that a catalyst system comprised of Pd(OAc) 2 , DMSO and 2 equivalents of benzoquinone was able to selectively catalyse an allylic C-H oxidation reaction of a monosubstitued olefin (Figure 29 50 top). 105,106 The authors noticed that the reaction without DMSO gave a mixture of addition products and therefore developed and tested compounds 48, which comprise ethylene-bridged bissulfoxides ligands 17b and 17e and Pd(OAc) 2 , in these reactions.…”
mentioning
confidence: 99%
“…100 Related examples where DMSO has been used as an additive in palladium catalysed reactions have appeared and while we do not intend to cover these cases due to the unclear role DMSO is playing in these reactions, selected examples can be found in the reference section. 103,104 Palladium bissulfoxide systems in catalysis 45 In initial work, White and co-workers showed that a catalyst system comprised of Pd(OAc) 2 , DMSO and 2 equivalents of benzoquinone was able to selectively catalyse an allylic C-H oxidation reaction of a monosubstitued olefin (Figure 29 50 top). 105,106 The authors noticed that the reaction without DMSO gave a mixture of addition products and therefore developed and tested compounds 48, which comprise ethylene-bridged bissulfoxides ligands 17b and 17e and Pd(OAc) 2 , in these reactions.…”
mentioning
confidence: 99%
“…20 In 2014, Srinivas groups have demonstrated a miscellaneous protocol toward the synthesis of disubstituted 2,3-dihydroazanaphthoquinones 33 by the consecutive oxidation of an alkyne and the hydration of a nitrile group of 2-alkynylarylnitrile 1 (Scheme 18). 21 The mechanistic pathway was initiated by the coordintion of an activated palladium complex with both alkyne and nitrile groups of substrate 1 to generate species I. The triple bond of species I was attacked by another dimethyl sulfoxide (DMSO) molecule to furnish species II, which further converted to species III in the presence of water.…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“…On the other hand, 2-alkynylbenzamide is a versatile dual-functional synthon toward many privileged skeletons, such as isoquinolin-1-ones, isoindolin-1-ones, isocoumarin-1-imines, and isobenzofuran-1-imines . For 2-alkynylbenzamide-based chemistry, regiochemistry in N / O nucleophilicity and 5-exo cyclization/ 6-endo cyclization was still challenging.…”
Section: Introductionmentioning
confidence: 99%
“…According to our recent findings, the metal-free radical annulation of 2-alkynylbenzamide dominated in an O -nucleophilic cyclization manner, which served as an important supplement of electrophilic cyclization . Given the high importance of the isoquinolin-1-one structural core, many research groups devoted themselves to its synthetic methodology development. , To the best of our knowledge, a few developed cases starting from 2-alkynylbenzamide indicated that using indium salt , and platinum salt as Lewis acid catalysts could convert 2-alkynylbenzamide into isoquinolin-1-one through N -nucleophilicity 6- endo cyclization. With catalytic Cu­(OAc) 2 and a stoichiometric inorganic base, a two-step procedure from 2-iodobenzamide and terminal alkyne also provided an isoquinolin-1-one core .…”
Section: Introductionmentioning
confidence: 99%